Pengaruh Etika Bisnis Islam Terhadap Minat Beli Konsumen di Pasar Induk Sangatta Utara - A. Almauizah; Imrona Hayati; Ajis Supangat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sangatta Central Market, one of the largest trading centers in North Sangatta, accommodates more than 750 traders and operates daily until midday, reflecting the high intensity of economic transactions in the region. Within this trading environment, Islamic business ethics play a pivotal role, particularly for Muslim traders, as they not only regulate commercial practices but also shape customer comfort and satisfaction. However, observations indicate that not all traders consistently practice ethical behaviors in line with Islamic values—for example, some neglect to maintain a friendly attitude such as smiling during interactions with buyers. This condition potentially reduces the quality of service and impacts consumer willingness to return. In response, this study seeks to analyze the influence of Islamic business ethics on consumer purchasing interest at the North Sangatta Central Market. The research adopts a quantitative approach by distributing structured questionnaires to a sample of 96 Muslim customers, complemented by direct observation and systematic data recording. The collected data were analyzed using simple linear regression to determine the extent to which the implementation of Islamic business ethics contributes to consumers’ willingness to shop. The results reveal a regression equation of Y' = 9.764 + 0.304X with a correlation coefficient (R) of 0.299. The coefficient of determination (R²) of 29.9% indicates that Islamic business ethics significantly and positively influence consumer purchasing interest. In other words, nearly one-third of the variance in customer purchasing interest can be explained by the level of ethical business practice applied by traders. This finding implies that the more traders integrate Islamic values—such as honesty, fairness, and friendly interaction—into their daily business practices, the more likely consumers are to engage in transactions and maintain loyalty to the market.